Persepsi Pengunjung terhadap Ketersediaan Sarana Penunjang Ruang Publik Kota Mara - Hartina Alwi; Mukti Ali (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
This study aims to determine the perceptions and preferences of visitors to the public space facilities in the Kota Mara. This research uses qualititave and quantitative research. The number of respondent is 210 samples. Sample selection uses nonprobability purposive sampling technique by means of type purposive and accidental sampling. Data were collected using observation method, and questionnaire with Likert Scale. Data analysis methods used is the frequency distribution analysis and multinomial regression analysis. The result of this study outlines that 1) Available means of support space Kota Mara, namely: achievement building, Islamic center, plaza/exhibition halls, parks/green corridors, pedestrian paths, bins and street vendor stalls. 2) Visitor perceptions of the availability of supporting facilities in the Public Space of Kota Mara among other: means of parking spaces is quite good, and the perception of visitors to the facilities building achievements, islamic center, plaza/exhibition halls, parks/green corridors, pedestrian paths, bins and street vendor stalls is good.